Effectivity of Dexamethasone Fighting Cytokine Storm in Severe COVID-19 Patients; Does it still reliable used for COVID-19? - Syahrul Tuba; Muhammad Rifly Aprianto (PT FORMOSA CENDEKIA GLOBAL, 2022)
Covid-19 has been declared a pandemic by WHO (World Health Organization) since March 2020. However, there is confusion about the therapy that should be used for covid-19. This virus enters the human body by binding to ACE-II receptors in the human body, causing an inflammatory response and a decrease in the body's immune response. The overproduction of pro-inflammatory cytokines relates to COVID-19's cytokine storm, also known as cytokine release syndrome (CRS). The aim of this article is to determine the effectiveness of dexamethasone in treating cytokine storms in severe COVID-19 patients using ventilator respiratory. This study used a narrative review journal from several leading platforms such as PubMed, NEJM, NCBI, and others, as well as from government websites, selected between 2019 and 2021 in the English language. Dexamethasone is a corticosteroid class of drugs that can act as anti-inflammatory and immunosuppressive. The drug inhibits the expression of genes that induce inflammatory proteins. In the case of severity covid-19, dexamethasone was used in patients who had decreased oxygen saturation. After being treated using this drug intravenously, the patient showed a positive increase in oxygen saturation levels. Dexamethasone therapy was effective and may have been acceptable in severe Covid-19 patients that actively ventilator respiratory. Then, a more rigorous investigation of the impact of dexamethasone is needed.